2019
DOI: 10.1088/2399-6528/ab360f
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Gross–Pitaevskii solutions of harmonically confined BEC gases in reduced dimensions

Abstract: By exact numerical solutions of the Gross-Pitaevskii (GP) equation in 3D, we assess the validity of 1D and 2D approximations in the study of Bose-Einstein condensates confined in harmonic trap potentials. Typically, these approximations are performed when one or more of the harmonic frequencies are much greater than the remaining ones, using arguments based on the adiabatic evolution of the initial approximated state. Deviations from the 3D solution are evaluated as a function of both the effective interaction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Therefore, if we set Ψ 0α (r, t) = ψ 0 ( r)ζ α (t) with ζ α (t) a simple threecomponent spinor, we can integrate out the spatial part and find very simple dynamical equations, called SMA-GP (not shown here), for the time evolution of ζ(t). The result of those is shown also in Figure 1 where we plot the time evolution of the magnetization f (t) = drΨ * 0α (r, t)F αβ Ψ * 0α (r, t) with full 3D GP (see [39] for the details of our methods), and…”
Section: An F = 1 Sbec Within the Sma Approximation-full Quantum Diagonalizationmentioning
confidence: 85%
“…Therefore, if we set Ψ 0α (r, t) = ψ 0 ( r)ζ α (t) with ζ α (t) a simple threecomponent spinor, we can integrate out the spatial part and find very simple dynamical equations, called SMA-GP (not shown here), for the time evolution of ζ(t). The result of those is shown also in Figure 1 where we plot the time evolution of the magnetization f (t) = drΨ * 0α (r, t)F αβ Ψ * 0α (r, t) with full 3D GP (see [39] for the details of our methods), and…”
Section: An F = 1 Sbec Within the Sma Approximation-full Quantum Diagonalizationmentioning
confidence: 85%
“…The values of the effective interaction couplings g σσ with σ, σ = {↑, ↓} are written in terms of the s-wave scattering length a σ,σ as, g σσ = 4πN 2 a σσ /m, being N the number of particles in the condensate. We should point here that these interaction coefficients must be substituted by effective interaction couplings that take into account that the atom collision processes occur in 2D [25][26][27][28][29][30][31]. The effective scattering length in the plane x − y becomes a σσ → a σσ / √ 2πl z , with l z = /mω z , being ω z a typical frequency of condensates confined in 2D [32,33].…”
Section: Model and Initial State Preparationmentioning
confidence: 99%
“…Although not shown here for brevity, we have performed full evolution of an F = 1 Gross-Pitaevskii equation, in the ferromagnetic regime, and found that SMA holds perfectly well for uniform magnetic fields, see Ref. [30] for details of our method.…”
Section: Introductionmentioning
confidence: 99%